Evaluating the dual-task decrement within a simulated environment: Word recall and visual search. (January 2023) - Jackson, Kenneth M.; Shaw, Tyler H.; Helton, William S.
Abstract: Simulated environments have become better able to replicate the real world and can be used for a variety of purposes, such as testing new technology without any of the costs or risks associated with working in the real world. Because of this, it is now possible to gain a better understanding of cognitive demands when working in operational environments, where individuals are often required to multitask. Multitasking often results in performance decrements, where adding more tasks can cause a decrease in performance in each of the individual tasks. However, little research investigated multitasking performance in simulated environments. In the current study we examined how multitasking affects performance in simulated environments. Forty-eight participants performed a dual visual search and word memory task where participants were navigated through a simulated environment while being presented with words. Performance was then compared to single-task performance (visual search and word memory alone). Results showed that participants experienced significant dual-task interference when comparing the dual-tasks to the single-tasks and subjective measures confirmed these findings. These results could provide useful insight for the design of technology in operational environments, but also serve as an evaluation of MRT in simulated environments.